Efficacy of pentamidine analogue 6 in dogs with chronic atrial fibrillation. (5th August 2018) - Szatmári, Viktor; Ji, Yuan; Herwijnen, Bianca van; Feng, Mei; Wang, Michael Zhou; Bossu, Alexandre; van der Heyden, Marcel A. G.
Abstract : Background: The inward rectifier inhibitor pentamidine analogue 6 (PA‐6) is effective in cardioversion of goats with persistent rapid pacing induced atrial fibrillation (AF) and is not proarrhythmic in dogs with experimental chronic 3rd‐degree AV block. Efficacy and safety in the clinical setting are unknown. Hypothesis: That PA‐6 would be effective in converting AF to sinus rhythm (SR) in dogs with naturally occurring AF, without the presence of overt adverse effects. Animals: Ten client‐owned large and giant breed dogs. Methods: Animals with persistent or permanent AF were recruited for our prospective study. PA‐6 was administered IV as a bolus of 2.5 mg/kg 10 min −1 followed by a maintenance infusion of 0.04 mg/kg min −1 for a maximum of 50 minutes in conscious dogs. Standard 6 lead limb ECG was recorded during the infusion. Visible and audible signs of adverse effects were scored during the entire procedure. Results: PA‐6 did not induce changes in QRS duration (54.7 ± 4.6 versus 56.7 ± 6.1 ms, P = .42), QTc interval (241.1 ± 19.5 versus 258.7 ± 19.8 ms, P = .061) or RR interval (363.4 ± 84.6 versus 440.8 ± 96.3 ms, P = .072) at the end of the bolus. No cardioversion to SR was observed in any dog. Three dogs displayed no adverse effects. Five dogs had premature ventricular depolarizations during PA‐6 infusion on the ECG. Respiratory distress with laryngeal stridor, subtle muscle twitching, and mild generalized muscular weakness were noncardiac adverse effects observed in 5 dogs. Adverse effects resolved spontaneously. Conclusions and Clinical importance: Chronic naturally occurring AF in large and giant breed dogs could not be cardioverted to SR by PA‐6.